(untitled) (Khairulummah, 2021)
Allah revealed the Noble Qur’an To His prophet (PBUH) and that is an evidence for the truthfulness of his prophet hood .Allah make a special sequence in this book and he taken the responsibility of its protection, there are scholar whom devoted their lives for the understanding and explanation of the meaning of this Noble book, So All of these Scholar’s explained the verses of Qur’an by their vision, level of understanding, thinking and keeping in view the demands of the place and time. That is the reason that we are finding their different views in the interpretation of Qur’an. In this Article discussed these types of differences and its kinds that we may understand the reality of these various opinions in Tafseer. That these are just the differences in words or there is contradiction in real in their views?